Corporate Social Responsibility as Economic Mechanism for Creating Firm Value - Sam Ronald; Suwandi Ng; Fransiskus Eduardus Daromes (Universitas Pasundan, 2019)
This research is aimed to investigate the influence of corporate social responsibility (CSR) on financial variables such as financial constraints, risks and earnings quality as a mediating aspects for creating firm value. Data were collected from manufacturing companies listed on the Indonesia Stock Exchange for 2013–2016. By using regression and path analysis method, the result shows that CSR has a significant influence on increasing firm value. Meanwhile, the indirect influences show that financial constraints and risk have a positive mediating role in the relationship between CSR and firm value, while the quality of earnings has no mediating role. The finding reveals a difference result with previous studies that CSR has an influence on reducing firm risk. Conflict of stakeholder interest exists as the result of excessive CSR activities and trading noise are used to explain this relationship. This study also indicates that cash flow has better role in increasing firm value compared to the accounting earnings of firm.